ABIN1 Inhibits Inflammation through Necroptosis-Dependent Pathway in Ulcerative Colitis - Jing Bao; Bin Ye; Yuhan Ren (Genetics Research)
Background. Ulcerative colitis (UC) is characterized by chronic, recurrent intestinal inflammation and intestinal epithelial injury including a wide range of epithelial cell death, ulcers, crypt abscesses, and the formation of fibrosis. The intestinal barrier dysfunction runs through the whole process of the occurrence and development of UC. A recent study revealed that an ubiquitin binding protein ABIN1 played a role in tissue homeostasis and autoimmunity diseases which involved in the anti-inflammatory response of intestinal epithelia cells. However, the roles of ABIN1 in ulcerative colitis pathogenesis remain unclear. Methods. The mRNA and protein expression level of ABIN1 and necroptosis-associated genes (RIPK1, RIPK3, and MLKL) were conducted to investigate the relationship between ABIN1 and necroptosis in clinical UC specimens. Subsequently, the dextran sodium sulfate (DSS)-induced mice colitis model was used to verify the ABIN1 function in vivo. Furthermore, we established ABIN1 gain and loss function assay in CACO-2 to confirm the mechanism in UC in vitro. Results. We found that ABIN1, RIPK1, RIPK3, and MLKL were upregulated in UC sample and DSS-induced colitis. Upon TNF-α stimulation in the intestinal epithelia cell line, overexpression of ABIN1 significantly inhibits necroptosis in the intestinal inflammation model along with the reduction expression of pro-inflammatory cytokines such as IL1B, IL6, IL8, and TNF-α. Blocking RIPK1 by Nec-1s in vivo and in vitro dramatically alleviated the colitis and cell death which shares the same phenotype with ABIN1 overexpression. Conclusion. Hence, the dysregulation of ABIN1 may relate to the uncontrolled necroptosis and inflammation in UC, and negatively regulate the occurrence and process of ulcerative colitis. ABIN1 activation may be considered a therapeutic strategy for UC.